Implementation of Internet of Things for Battery Room Monitoring and Controlling (Case Study PT. Telkom Indonesia-Malang) - Haq, Nabilah Nurul; Rakhmania, Amalia Eka; Mustafa, Lis Diana (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Batteries are capable of storing and conducting electric current, as a backup power supply source in the industry. Battery charging involves the conversion of electrical energy into chemical energy, and overcharging produces harmful hydrogen sulfide gas(H?S), which is crucial for early risk identification. This study aims to develop a condition monitoring system using the Internet of Things in industrial areas. This research was developed in the battery room owned by Telkom Malang, adapted to the need to optimize the condition of the battery room. The research system integrates the mq136 sensor for detecting H?S gas, DHT22 for temperature and humidity, and a voltage sensor that measures battery capacity. All data is processed by the ESP32 microcontroller, stored on Firebase, and displayed through the website to make it easier for officers to monitor and control the battery room. The result of DHT22 sensor accuracy for temperature is 98.82%, humidity is 98.83% and voltage sensor accuracy is 99.95%. As for the mq136 gas sensor, it has an accuracy value of 93.5%. The automatic fan control system has been effective in activating the fan when the battery chamber conditions indicate H?S gas levels above 10 ppm and temperatures above 40°.